FORMULASI DAN KARAKTERISASI NANO FITOSOM ANTIDIABETES DARI EKSTRAK ETANOL BUAH MENGKUDU (Morinda Citrifolia L.) DENGAN METODE HIDRASI LAPIS TIPIS - Amrina Rosyada; Noval; Febby Yulia Hastika; Setia Budi; Dwi Rizki Febrianti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Diabetes mellitus causes high blood sugar levels due to pancreatic metabolic disorders. Noni fruit (Morinda Citrifolia L.) with xeronine content is used. This study created a New Drug Delivery System (NDDS) based on nanophytosomes to overcome blood glucose metabolism problems. Nanophytosomes encapsulate active substances from plant extracts (phytoconstituents) with lipids or phospholipids such as phosphatidylcholine for easier absorption and use. This study examined the formulation results and the effects of cholesterol on noni fruit extract nanophytosomes. This study used a quasi-experimental design, one group posttest. Thin film hydration was used to create nanophytosomes with different cholesterol contents from noni fruit extract. The research formula meets the requirements with particle size results of 271.3-501.3 nm (p-0.24), polydispersity index of 0.614-1.902 nm (p-0.947), zeta potential -10.8 - (-21.7) mv (p-0.998), adsorption efficiency of 70.83%-92.66% (p-1.000), and non-spherical surface morphology. The evaluation results show that F2 with a cholesterol concentration of 1.5 g is a good formula because it has an adsorption efficiency of 92.66% and a fine particle size.